(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Aim: The main aim of this research is to evaluate the surface roughness of Sisal/Glass fiber reinforced epoxy composite filled with novel Drumstick Gum Powder and compare it with Sisal/Glass fiber epoxy composite. Materials and Methods: In this study, the Sisal/Glass fiber epoxy composite was taken as a control group which has 20 sample specimens. Also, Sisal/Glass fiber with 20% filled reinforced epoxy composites was considered as an experimental group which also has 20 sample specimens.The samples were calculated based upon G Power. G Power is taken as 80%. Composites plates were prepared by hand layup method with 20% drumstick gum powder novel bio-filler and without filler. Results: Surface roughness of Sisal/Glass fiber without filler reinforced epoxy composite is 4.00 µm. Sisal/Glass fiber with 20% filler epoxy composite is 3.03 µm. sisal/Glass fiber with 20% filler showed a significant value p= 0.000 (p<0.05) than Sisal/Glass fiber epoxy composite. Conclusion: Within the limitations of this study, the surface roughness of Sisal/Glass fiber with a 20% volume fraction of drumstick gum powder filler reinforced epoxy composite exhibited improvement in surface finish than the Sisal/Glass fiber epoxy composite.